Temperature dependence of the scanning performance of an electrostatic microscanner. (20th January 2016) - Ishikawa, Noriaki; Ikeda, Kentaro; Sawada, Renshi
Abstract: An optical microscanner is one examples of an optical-MEMS device, which scans a laser beam across one or two dimensions by reflecting it. The microscanner has a range of applications, such as laser printers, laser displays and bio-medical imaging. For each application, the mirror is required to oscillated at a certain frequency and optical scan angle. However, its scanning performance varies with temperature. To address this issue, the temperature dependence of the natural frequency of a 1D electrostatic microscanner formed of single-crystal silicon is investigated both theorectically and experimentally in this paper. As the temperature rises from 30 °C to 80 °C, the calculated value of the natural frequency decreased from 1910.81 Hz to 1908.68 Hz, and the experimental value decreased from 2123.85 Hz to 2120.56 Hz. The percentage changes in calculated and experimental results were −0.11% and −0.15%, and thus the former was consistent with the latter. The factors of the variation of natural frequency are the deformation caused by thermal expansion and the temperature dependence of shear modulus. The results of theoretical calculations indicated that the principal factor in the change of natural frequency was the shear modulus on the temperature.